2001
DOI: 10.4049/jimmunol.167.10.6021
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironment Produced by Acute Myeloid Leukemia Cells Prevents T Cell Activation and Proliferation by Inhibition of NF-κB, c-Myc, and pRb Pathways

Abstract: Tumors produce a variety of immunosuppressive factors which can prevent the proliferation and maturation of a number of normal hemopoietic cell types. We have investigated whether primary acute myeloid leukemia (AML) cells have an effect on normal T cell function and signaling. Tumor cell supernatant (TSN) from AML cells inhibited T cell activation and Th1 cytokine production and also prevented activated T cells from entering the cell cycle. These effects occurred in the absence of AML cell-T cell contact. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
114
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(115 citation statements)
references
References 72 publications
0
114
0
1
Order By: Relevance
“…It has been reported that malignant cells of both solid tumors and leukemias produce factors that inhibit cells of the immune system, which may help them evade immune surveillance. 1 In the present study, we examined whether the previously noted specific effects on T-cell cytokine production, cell cycle inhibition, pRb phosphorylation, c-Myc induction and apoptosis are exclusive to AML cells, or occur in other lower grade myeloid malignancies, namely MDS and chronic phase (CP) CML.…”
Section: Acknowledgementsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that malignant cells of both solid tumors and leukemias produce factors that inhibit cells of the immune system, which may help them evade immune surveillance. 1 In the present study, we examined whether the previously noted specific effects on T-cell cytokine production, cell cycle inhibition, pRb phosphorylation, c-Myc induction and apoptosis are exclusive to AML cells, or occur in other lower grade myeloid malignancies, namely MDS and chronic phase (CP) CML.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…2 AML TSN prevents T-cell activation by profoundly inhibiting the production of the Th1 cytokines IFN-g and IL-2 and inhibits cell cycle entry before the G 0 -G 1 commitment point, 3 by preventing the phosphorylation of retinoblastoma protein (pRb) and the induction of c-Myc. 1 In addition, AML TSN delays the apoptosis of both normal hematopoietic and leukemic blast cells; 2 however, it was unknown as to whether this is a unique feature of AML or extended to other myeloid malignancies. We now show that T-cell apoptosis is inhibited by TSN from the cells of 11/12 cases of chronic myeloid leukemia (CML) and myelodysplastic syndrome (MDS) tested, irrespective of disease severity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Defective activation of NF-B has been reported in T cells from tumor-bearing mice and cancer patients (12)(13)(14). The deficiency stems from impaired nuclear localization of the RelA/p50 heterodimer, a problem that has been noted in both tumor-infiltrating lymphocytes (TIL) 3 and peripheral blood T cells isolated from patients with renal cell carcinoma (RCC) (15)(16)(17).…”
mentioning
confidence: 99%
“…3,4,11 Even if a proportion of leukaemic cells were able to mature into normal functioning DC, the remaining leukaemic blasts in the microenvironment 12 may directly inhibit presentation of antigen to autologous T cells by an ill-defined contactindependent mechanism, although cytolytic function may be maintained. 13 Prior to the ability to distinguish T cells from B cells in blood lymphocytes, it was suggested that patients with AML were immunocompromised based on low numbers of circulating lymphocytes and suppressed DTH reaction to stimulus. 10 This study had led to the prevailing view of immune dysfunction in AML.…”
mentioning
confidence: 99%